Prevalence of anemia amongst overweight and obese children in NCT of Delhi - Kapil, Umesh; Sareen, Neha (Indian Journal of Community Health, 2014)
Introduction: Anemia amongst children has been associated with impaired cognitive functions, developmental delays, behavioral and learning disturbances. Young children from high-income groups could be also being affected from anemia. Objective: To assess the prevalence of anemia amongst overweight and obese children in the age group of 5-18 years residing in National Capital Territory (NCT) of Delhi. Material and Methods: Total of 413 children was included in the present study. The hemoglobin (Hb) estimation was done by cyanmethemoglobin method. Results: In the age group of 5-11 years, the prevalence of anemia amongst overweight and obese children was found to be 38.4% and 29.2%. And in the age group of 12-18 years, the prevalence of anemia amongst overweight and obese children was found to be 33.3% and 21.7%; respectively. Conclusion: The findings of the present study revealed that there is a high prevalence of anemia amongst overweight and obese children in the age group of 5-18 years in NCT, Delhi.